Silica stable isotopes and silicification in a carnivorous sponge Asbestopluma sp. - Hendry, K.R.; Swann, George E.A.; Leng, Melanie J.; Sloane, Hilary J.; Goodwin, C.; Berman, J.; Maldonado, M. (European Geosciences Union, 2015)
The stable isotope composition of benthic sponge spicule silica is a potential source of palaeoceanographic information about past deep seawater chemistry. The silicon isotope composition of spicules has been shown to relate to the silicic acid concentration of ambient water, although existing calibrations do exhibit a degree of scatter in the relationship. Less is known about how the oxygen isotope composition of sponge spicule silica relates to environmental conditions during growth. Here, we investigate the vital effects on silica, silicon and oxygen isotope composition in a carnivorous sponge, Asbestopluma sp., from the Southern Ocean. We find significant variations in silicon and oxygen isotopic composition within the specimen that are related to unusual spicule silicification. The largest variation in both isotope systems was associated with the differential distribution of an unconventional, hypersilicified spicule type (desma) along the sponge body. The absence an internal canal in the desmas suggests an unconventional silicification pattern leading to an unusually heavy isotope signature. Additional internal variability derives from a systematic offset between the peripheral skeleton of the body having systematically a higher isotopic composition than the internal skeleton. A simplified silicon isotope fractionation model, in which desmas were excluded, suggests that the lack of a system for seawater pumping in carnivorous sponges favours a low replenishment of dissolved silicon within the internal tissues, causing kinetic fractionation during silicification that impacts the isotope signature of the internal skeleton. Analysis of multiple spicules should be carried out to "average out" any artefacts in order to produce more robust downcore measurements.